Рецензія на книгу “Леонід Рубцов – видатний ландшафтний архітектор” О.Л. Рубцової та Н.В. Чувікіної - Klymenko, Yurii (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2021)
A monograph devoted to the life and work of the outstanding landscape architect Leonid Ivanovich Rubtsov has been recently published. The book provides information about the projects developed and implemented by professor Rubtsov, as well as the main theoretical principles of landscape architecture, which were proposed by him.